2009
DOI: 10.2320/matertrans.mra2008329
|View full text |Cite
|
Sign up to set email alerts
|

Fe/Ni Cluster Hybrid Material Produced by Double Glow Discharge Sources

Abstract: Fe and Ni clusters have been simultaneously deposited on substrates using an improved plasma-gas-condensation cluster deposition apparatus, and investigated by transmission electron microscopy, X-ray photoelectron spectroscopy and magnetometry. In these Fe/Ni cluster hybrids Fe and Ni clusters are randomly mixed, where bcc Fe and fcc Ni diffraction rings are detected, and their lattice constants are almost same as those of pure Fe and Ni metals. The peak positions of core-levels, Fe-2p 3=2 and Ni-2p 3=2 lines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…[ 9b ] In fact, the single study on nt‐Cu in contention, [ 9a ] reporting some nanotwin stability up to 800 °C, refers to unintended Fe nanoparticles (deposition impurities) visible in a subset of TEM images, that may fortuitously play an equivalent stabilising role to W NP here. In contrast to pure nt‐Cu, the high W NP addition leads to nanotwin retention well beyond a simple Zener pinning law, with better stability than can be expected for these initially over‐refined, homogeneous microstructures: [ 33 ] no measurable increase in TB spacing is found after heating to 400 °C, within error. One may even speculate that the W NP also lead to regeneration of nanotwins upon strain‐induced dynamic recrystallization of the as‐deposited microstructure (purple arrows, Figure 3).…”
Section: Discussionmentioning
confidence: 98%
“…[ 9b ] In fact, the single study on nt‐Cu in contention, [ 9a ] reporting some nanotwin stability up to 800 °C, refers to unintended Fe nanoparticles (deposition impurities) visible in a subset of TEM images, that may fortuitously play an equivalent stabilising role to W NP here. In contrast to pure nt‐Cu, the high W NP addition leads to nanotwin retention well beyond a simple Zener pinning law, with better stability than can be expected for these initially over‐refined, homogeneous microstructures: [ 33 ] no measurable increase in TB spacing is found after heating to 400 °C, within error. One may even speculate that the W NP also lead to regeneration of nanotwins upon strain‐induced dynamic recrystallization of the as‐deposited microstructure (purple arrows, Figure 3).…”
Section: Discussionmentioning
confidence: 98%
“…1). 12,13) After setting Fe and Si (doped with 10 À2 %Al) disc plates (80 mm in diameters and 5 mm in thicknesses) on the target holders of the sputtering rooms 1 and 2, these rooms were evacuated down to 3 Â 10 À4 Pa and the intermediate room down to 3 Â 10 À5 Pa by a compound molecular pump, CMP (not shown in Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…1). 12) In the improved PGCCD system, Fe and Si clusters are juxtaposed by setting the partition plate, while Fe-rich coreSi rich shell clusters are formed without setting the partition plate. Moreover, the chemical analyses have suggested that the cores are bcc Fe or heterogeneous bcc Fe-Si alloys, their diameters increasing with the overall cluster sizes, and the shells are 2 nm thin amorphous Si layers.…”
Section: Introductionmentioning
confidence: 99%